2011
DOI: 10.1111/j.2041-210x.2011.00095.x
|View full text |Cite
|
Sign up to set email alerts
|

A measure for describing and comparing postreproductive life span as a population trait

Abstract: Summary 1. While-classical life-history theory does not predict post-reproductive lifespan (PRLS), it has been detected in a great number of taxa, leading to the view that it is a broadly conserved trait, and attempts to reconcile theory with these observations. We suggest an alternative: the apparently wide distribution of significant PRLS is an artifact of insufficient methods. 2. PRLS is traditionally measured in units of time between each individual’s last parturition and death, after excluding those indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
122
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(125 citation statements)
references
References 39 publications
3
122
0
Order By: Relevance
“…The PrR value of 0.13 calculated for Myanmar elephants is higher than those found in primates living in wild or semi-wild conditions ( Pan troglodytes 0.018; Papio hamadryas 0.084; Macaca fuscata 0.055) (Figure 5) and corresponds to values found in many zoo populations of primates [36]. The value, 0.51, calculated for Finnish women correspond with patterns found in other historical or hunter-gatherer populations [36], where PrR ranges from 0.3 to 0.47 (in modern populations <0.76).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The PrR value of 0.13 calculated for Myanmar elephants is higher than those found in primates living in wild or semi-wild conditions ( Pan troglodytes 0.018; Papio hamadryas 0.084; Macaca fuscata 0.055) (Figure 5) and corresponds to values found in many zoo populations of primates [36]. The value, 0.51, calculated for Finnish women correspond with patterns found in other historical or hunter-gatherer populations [36], where PrR ranges from 0.3 to 0.47 (in modern populations <0.76).…”
Section: Discussionmentioning
confidence: 85%
“…Post-reproductive representation values and maximum longevities in Asian elephants and humans from this study, other PrR-values according to Levitis and Lackey 2011 [36]. Maximum longevities in Macaca fuscata from [44], Pan troglodytes from [45], Papio hamadryas from [46] and Globicephala macrorhyncus from [47].…”
Section: Discussionmentioning
confidence: 86%
“…The 90th percentiles of these two distributions are quite similar for the nonhuman primates, but they are quite different for the !Kung (Table S5). Finally, comparison of the postreproductive representation of adults (3,12) in the nonhuman primates and humans is also striking: among the nonhuman primate species, 1-6% of adult-female-years are lived by postreproductive individuals, whereas in the !Kung this metric reaches 42.5% (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Levitis et al (3) examined reproductive senescence in humans and in three nonhuman primate species, and concluded that the postfertile lifespan is a distinct life phase that occurs in humans but may be absent in many (but not all) other animals. The authors address the problem of how to identify a true postfertile lifespan from the occasional occurrence of postfertile individuals in a population (12). This approach also highlights the fact that to place humans precisely on the comparative landscape, data from wild populations and from multiple species of primates and other mammals are required.…”
mentioning
confidence: 99%
“…The hunter-gatherer groups included in the Siler fit are the Hadza, Ache Forest, Hiwi, !Kung, and Agta. The (37) and were also analyzed by Levitis and Lackey (38).…”
Section: Methodsmentioning
confidence: 99%